Super-Pangenome by Integrating the Wild Side of a Species for Accelerated Crop Improvement. (February 2020) - Khan, Aamir W.; Garg, Vanika; Roorkiwal, Manish; Golicz, Agnieszka A.; Edwards, David; Varshney, Rajeev K.
Abstract : The pangenome provides genomic variations in the cultivated gene pool for a given species. However, as the crop's gene pool comprises many species, especially wild relatives with diverse genetic stock, here we suggest using accessions from all available species of a given genus for the development of a more comprehensive and complete pangenome, which we refer to as a super-pangenome. The super-pangenome provides a complete genomic variation repertoire of a genus and offers unprecedented opportunities for crop improvement. This opinion article focuses on recent developments in crop pangenomics, the need for a super-pangenome that should include wild species, and its application for crop improvement. Highlights: Pangenome studies conducted so far have been limited mainly to one species and mostly cultivated accessions. The challenge with the current pangenomes is lack of representation of genomic diversity at the genus level. Crop wild relatives possess unearthed genetic diversity that has been lost during domestication and breeding. Pangenomics of crop wild relatives is the way forward to catalogue the complete gene repertoire of a genus. The super-pangenome is the approach of developing a pangenome of the pangenomes of different species for a given genus. Currently available methods and tools to develop pangenomes are mainly restricted to bacterial (prokaryotic) genomes. It is important now to develop novel, effective, and user-friendly tools for the development of super-pangenomes for crop (eukaryotic) genomes.